Modernizing the registration of psychotropic drugs: Ordinance 344/98 needs to be updated - Oliveira Rodrigues, Cássio Alexandre; Pinheiro Lopes, Higor José (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Over the past three decades, the world has undergone significant changes and technological advances that have enabled automation and, consequently, improvements in work processes. These developments have optimized information management, reduced workloads and bu reaucratic barriers—particularly in contexts with limited human re sources—and thereby decreased operational time in daily routines.¹⁻² In health services, especially within hospital care, it has been possible to observe the refinement and adaptation of these processes in response to the exponential increase in healthcare demands during and after the COVID-19 pandemic.³ Furthermore, over the years, the perspectives of healthcare services have shifted, and the quality of service delivery and patient safety have become the guiding principles of healthcare practi ces.⁴ These factors have been decisive in driving the computerization of certain tasks, which today represents an indispensable condition for the proper functioning of processes within health services. The same has occurred in hospital pharmacy; however, not all aspects related to it have progressed equally.